Perlindungan Hukum Tanah Sengketa: Urgensi Doktrin Lis Pendens dalam Reformasi Hukum Acara Perdata Indonesia - Susilo, Erwin (Universitas Medan Area, 2025)
This article aims to examine the urgency of applying the doctrine of lis pendens in civil land dispute cases in Indonesia, particularly to provide legal protection for disputing parties and third parties against the risk of land rights transfer over disputed property during court proceedings. This research employs a normative juridical method with statutory, conceptual, and comparative approaches. The legal systems of India and England are selected as comparators, as they have explicitly implemented the doctrine of lis pendens through legislation and case law, especially in terms of third-party protection, effectiveness in preventing the transfer of disputed objects, and case registration systems. The findings indicate that Indonesian civil procedural law does not yet have an automatic mechanism to prohibit the transfer of disputed objects during ongoing proceedings, resulting in a legal vacuum. The main contribution of this study is to propose the application of the lis pendens doctrine through the establishment of new procedural norms, the development of a court case information administration system, and public awareness campaigns on precautionary principles in land transactions. The study recommends the enactment of legal norms prohibiting land transfers during the judicial process.